The practical SQL handbook : using SQL variants - Bowman, Judith S. (Addison-Wesley, 2001)
This latest edition of the best-selling implementation guide to the Structured Query Language teaches SQL fundamentals while providing practical solutions for critical business applications. The Practical SQL Handbook, Fourth Edition now includes expanded platform SQL coverage and extensive real-world examples based on feedback from actual SQL users. The Practical SQL Handbook begins with a step-by-step introduction to SQL basics and examines the issues involved in designing SQL-based database applications. It fully explores SQL's most popular implementations from industry leaders, Oracle, Microsoft, Sybase, and Informix. Highlights include: Detailed coverage of SQL commands for creating databases, tables, and indexes, and for adding, changing, and deleting data Using the SELECT command to retrieve specific data Handling NULL values (missing information) in a relational database Joining tables, including self joins and outer joins (ANSI and WHERE-clause syntax) Working with nested queries (subqueries) to get data from multiple tables Creating views (virtual tables) to provide customized access to data Using SQL functions A bonus CD-ROM contains a time-limited, full-feature version of the Sybase® Adaptive Server Anywhere"!software as well as the sample database, scripts, and examples included in the book. The Practical SQL Handbook is the most complete reference available for day-to-day SQL implementations. 0201703092B05222001